Preferential Rules of Origin in the Law of the WTO and PTAs : The Challenge of 3D Printing - Wade, Diana E., (International Law E-books Online, Collection 2026., 2025)
Where does a 3D printed good come from? This book examines preferential rules of origin within the context of advanced manufacturing, focusing on 3D printing. From a foundation in the legal and technical aspects of rules of origin, it explores why 3D printing implies reconsidering how materials, labour, and technology factor into the determination of the origin of a good and the risks and opportunities this brings to producers and traders. The book suggests revisiting rules of origin in PTAs and encourages the WTO to promote incorporating rules or origin and new production methods into a balanced trade framework that supports producers, traders, and consumers globally.